Near infrared dye loaded copper sulfide-apoferritin for tumor imaging and photothermal therapy. Issue 26 (17th April 2018) - He, Yuanyuan; Shen, Yuanzhi; Zhou, Siqi; Wu, Yihui; Yuan, Zhenwei; Wei, Chen; Gui, Lijuan; Chen, Yisha; Gu, Yueqing; Chen, Haiyan
Abstract : Development of photothermal agents for imaging-guided photothermal therapy (PTT) has been of great interest in the field of nanomedicine. Abstract : Development of photothermal agents for imaging-guided photothermal therapy (PTT) has been of great interest in the field of nanomedicine. CuS-apoferritin was prepared by a biomimetic synthesis method by using the inside cavity of apoferritin to control the size of CuS nanoparticles. Then, a water-soluble near infrared (NIR) dye (MBA) was bound with CuS-apoferritin, forming a nanocomplex (CuS-apoferritin-MBA) with greatly enhanced photothermal conversion efficiency compared to CuS-apoferritin. The unique optical behavior of CuS-apoferritin-MBA enables fluorescence imaging and photothermal therapy at separated optical wavelengths both, with optimized performances. CuS-apoferritin-MBA was then utilized as a photothermal agent for imaging-guided photothermal therapy in tumor-bearing mouse models. As revealed by in vivo fluorescence imaging, CuS-apoferritin-MBA showed high tumor uptake owing to an enhanced permeability and retention effect and the active targeting of apoferritin. In vivo photothermal therapy experiments indicated that tumors could be ablated by combining CuS-apoferritin-MBA with irradiation of an 808 nm laser. Thus, our work presents a safe, simple photothermal nanocomplex, promising for future clinical translation in cancer treatment.